Etnolog in celostno ohranjanje kulturne dediščine - Delak Koželj, Zvezda (Traditiones (Ljubljana), 2013)
The planners of contemporary international and domestic protection legislation have now also recognized the crucial roles of the ethnological perspective and conservator-ethnologists in processes of cultural heritage conservation. The well-established and the additional tasks of conservator-ethnologists are presented and substantiated through the protective legal framework and connected in the work programme model of conservator ethnologists. Heritage preservation should be mainly a mutual decision and obligation of agents, proprietors and experts as well as all other stakeholders. The selected cultural phenomena should be presented with the help of tried and tested, recognised or innovative solutions as possible development potential to planners at all levels, both vertical and horizontal.
Keywords: ethnology; Etnologija; Konservatorstvo; Kulturna dediščina; cultural heritage; etnologi